Big colon surgery, little incisions: Minimally invasive techniques in emergent colon surgery. Issue 1 (July 2020) - Forte, Dominic Mario; Sheldon, Rowan; Johnson, Eric; Steele, Scott R.; Martin, Matthew J.
Abstract : Supplemental digital content is available in the text.